2017
DOI: 10.3389/fphys.2017.00274
|View full text |Cite
|
Sign up to set email alerts
|

Trunk Muscle Activity during Drop Jump Performance in Adolescent Athletes with Back Pain

Abstract: In the context of back pain, great emphasis has been placed on the importance of trunk stability, especially in situations requiring compensation of repetitive, intense loading induced during high-performance activities, e.g., jumping or landing. This study aims to evaluate trunk muscle activity during drop jump in adolescent athletes with back pain (BP) compared to athletes without back pain (NBP). Eleven adolescent athletes suffering back pain (BP: m/f: n = 4/7; 15.9 ± 1.3 y; 176 ± 11 cm; 68 ± 11 kg; 12.4 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…According to our findings, there was no association between LBP incidence and peak vGRF or vGRF side-to-side asymmetry, measured in VDJ landing. In a cross-sectional investigation, Müller et al were also unable to find a difference in vGRFs of youth athletes with and without LBP [48]. Future studies should investigate if loading rate is associated with LBP, because it has been shown to be a stronger risk factor for lower extremity injuries than peak GRF [49].…”
Section: Discussionmentioning
confidence: 87%
“…According to our findings, there was no association between LBP incidence and peak vGRF or vGRF side-to-side asymmetry, measured in VDJ landing. In a cross-sectional investigation, Müller et al were also unable to find a difference in vGRFs of youth athletes with and without LBP [48]. Future studies should investigate if loading rate is associated with LBP, because it has been shown to be a stronger risk factor for lower extremity injuries than peak GRF [49].…”
Section: Discussionmentioning
confidence: 87%
“…The results of Mueller et al ( 2017 ) suggest an altered neuromuscular activation pattern (increased trunk muscle activity during drop landing) in adolescent athletes with BP. Their study recruited 11 adolescent athletes with BP and 11 controls into a cross-sectional study.…”
Section: How Should Results From Cross-sectional Designs Be Interpretmentioning
confidence: 96%
“…Statistical issues aside, it is problematic when a cross-sectional study design (which can offer nothing more than association) is used to imply both causality and treatment recommendations for BP. In the presence of only cross-sectional data and an absence of key known confounding variables, the conclusion “ For prevention and therapy, specific sensorimotor exercises addressing the transverse trunk muscles with e.g., 3-dimensional loading situations might be beneficial” (Mueller et al, 2017 ) is speculative. While cross-sectional data are useful in identifying associations, inferences regarding causality should not be made from these study designs (Stovitz et al, 2017 ).…”
Section: How Should Results From Cross-sectional Designs Be Interpretmentioning
confidence: 99%
See 2 more Smart Citations